ANALISIS PENDAPATAN DAN KEUNTUNGAN RELATIVE USAHATANI SAWI HIJAU (Brassica Juncea L ) DI DESA PAPE KECAMATAN BAJAWA KABUPATEN NGADA - Lusianus M. R. Foju; Maximilian M. J. Kapa; Fidelis Klau (Undana Press, 2021)
This research was conducted in Pape Village, Bajawa Sub District, Ngada Regency in April 2019. The objectives of this study were: To determine the income of green mustard (Brassica Juncea L) farming in Pape Village, Bajawa Sub District, Ngada Regency, determine the relative advantages of green mustard farming in Pape Village. Bajawa Sub District, Ngada Regency: knowing the BEP Production and BEP Prices for green mustard farming in Pape Village, Bajawa District, Ngada Regency.The method used in this research is the census method. because the population is small, namely 60 vegetable farmers. The types of data collected are primary data and secondary data.The results showed that: 1) The average area of ​​land ownership for vegetable farming was 17 acres. The labor used is labor in the family, the average cost of the mustard farmers is Rp. 5,540,228.The average income of the respondents was Rp. 29,632,689, with an R / C Ratio of Rp. 6,34, while the BEP of mustard farming production in Pape Village is 788.08 kg, and BEP Price is Rp. 1108,04.